El exilio centroamericano y su aporte a la Sociedad costarricense a partir de la Segunda mitad del siglo XX - Cuevas-Molina, Rafael (2024)
Historically, Costa Rica, as well as Mexico, have been receptive poles of Latin American exile in the region. Exile has been an enriching phenomenon for the receiving countries while drying out the expelling country. The consequences of the departure of professionals, intellectuals, and artists, generally the most enlightened minds, are paid for decades.  It is also necessary to know how to differentiate the characteristics of the different exiles, which generally arrive in waves for specific periods: there are massive ones that include expatriates who fall under other classifications, such as refugees, for example, or migrations, not always legal, that are incorporated into the labor force of the city and the countryside and permeate behaviors and customs of daily life in the city and the countryside. and customs of the daily life of the local working sectors. This essay is concerned with the contribution of Central American exiles, in general, to Costa Rica, specifically the cultural contribution, since, as I assert, Central Americans have been incorporated into Costa Rica in many different areas, and in some they are decisive as a labor force that sustains important productive and service tasks, which implies the possibility of economic approaches that, as I say, are beyond the scope of these reflections.